Catalyst Free Synthesis of Bis(Indolyl)Methanes and 3, 3‐Bis(Indolyl)oxindoles in Aqueous Ethyl Lactate. Issue 35 (12th December 2017) - Gao, Ge; Han, Yi; Zhang, Zhan‐Hui
Abstract: A highly efficient and environmentally friendly approach has been reported for the synthesis of bis(indolyl)methanes and 3, 3‐bis(indolyl)oxindoles by reacting of indoles with aldehydes or isatins in water‐ethyl lactate under ultrasound irradiation. This protocol presents the benefits of catalyst‐free, operational simplicity, short reaction time, high product yield, broad substrate scope and applicability for large‐scale synthesis. Abstract : A simple and efficient approach for the synthesis of bis(indolyl)methanes and 3, 3‐bis(indolyl)oxindoles in water‐ethyl lactate under ultrasound irradiation is established. As the synthetic methods for these derivatives are rich, this method does not require any catalyst, and can well complement the existing methods.